2012
DOI: 10.1002/asia.201200222
|View full text |Cite
|
Sign up to set email alerts
|

Nanowire Transistor‐Based Ultrasensitive Virus Detection with Reversible Surface Functionalization

Abstract: We have applied a reusable silicon nanowire field-effect transistor (SiNW-FET) as a biosensor to conduct ultrasensitive detection of H5N2 avian influenza virus (AIV) in very dilute solution. The reversible surface functionalization of SiNW-FET was made possible using a disulfide linker. In the surface functionalization, 3-mercaptopropyltrimethoxysilane (MPTMS) was first modified on the SiNW-FET (referred to as MPTMS/SiNW-FET), with subsequent dithiothreitol washing to reduce any possible disulfide bonding betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 37 publications
0
30
0
Order By: Relevance
“…In addition, above 2-fold signal changes on unmodified and APTMS-modified NW-MOSFETs were discovered in comparison with MPTMS modified NW-MOSFETs. It has been demonstrated that MPTMS-SAM modified on silicon NW-MOSFETs might form disulfide bonding between the mercapto groups of MPTMS [21]. As a consequence of the lower number of mercaptan groups of MPTMS on NWs, relatively minor signal responses to varied pH solutions are seen in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, above 2-fold signal changes on unmodified and APTMS-modified NW-MOSFETs were discovered in comparison with MPTMS modified NW-MOSFETs. It has been demonstrated that MPTMS-SAM modified on silicon NW-MOSFETs might form disulfide bonding between the mercapto groups of MPTMS [21]. As a consequence of the lower number of mercaptan groups of MPTMS on NWs, relatively minor signal responses to varied pH solutions are seen in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, pH 2 solution protonated the surface of APTMS-modified NW-MOSFETs and resulted in significantly increasing voltage change in p-type devices [4]. Relatively smaller signal of MPTMS-modified NWs may be attributed to less well-ordered functional mercapto groups [21] and rather hydrophobic property [23]. The experiment of pH sensing showed our MOSFETs well performed in normal PBS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such work revealed the potential for the simultaneous detection of multiple viruses at the single virus level. In addition, an ultrasensitive detection of H5N2 avian influenza virus (AIV) has been realized by using a strategy of reversible surface functionalization of SiNW-FET in a dilute solution (Chiang et al 2012). A disulfide linker that reversibly controls the surface modification of SiNW renders the SiNW-FET a reusable device for the fast detection of H5N2 AIV.…”
Section: Protein-virus Interactionsmentioning
confidence: 99%
“…By modifying the SiNW-FET surface with specific functional molecules [2], previous works have shown the high sensitivity of SiNW-FET in measuring pH [3], and detecting proteins [4], DNA [5], and even single virus particles [6]. In the research of Kim, the SiNW-FETs was transformed into a DNA detector by modifying the SiNW-FETs surface with 3aminopropyltriethoxysilane (APTES) to provide a biochemical probe layer on the SiNWs [4].…”
Section: Introductionmentioning
confidence: 99%